Pengaruh Pandemi Virus Corona dan Informasi Akuntansi terhadap Kelangsungan Usaha Mikro, Kecil, dan Menengah - Nia Pratiwi; Rahman Sastrawan; Chornolius Hendreo (Jurusan Akuntansi Politeknik Negeri Pontianak, 2021)
The purpose of this study was to see the effect of the coronavirus pandemic and accounting information on business continuity. The method of this research is the level of clarity (explanatory) and this type of research is quantitative by conducting surveys and distributing questionnaires to MSME actors in Kapuas District. After the respondent fills out the questionnaire, the data will be processed and presented in the form of a Likert scale. Respondents in this study were SMEs in Kapuas District in Sanggau District. The results of this study show that the independent variables jointly affect business continuity (MSMEs), while partially the product selling price and cost of production have a significant effect on the business continuity variable (MSMEs). For the variables of the corona pandemic, financial reports, and effective planning do not affect business continuity. This study also shows that the influence of independent variables on business continuity (MSMEs) has a figure of 27.7%, for the rest it has a figure of 72.3% caused by other factors.